Vitamin E and changes in serum alanine aminotransferase levels in patients with non‐alcoholic steatohepatitis - Hoofnagle, J. H.; Natta, M. L.; Kleiner, D. E.; Clark, J. M.; Kowdley, K. V.; Loomba, R.; Neuschwander‐Tetri, B. A.; Sanyal, A. J.; Tonascia, J. (Alimentary pharmacology & therapeutics, 2013)
Summary Background Non‐alcoholic steatohepatitis (NASH) is a common cause of serum alanine aminotransferase (ALT) elevations and chronic liver disease, but it is unclear how well ALT elevations reflect the liver injury. Aim To assess how well changes in ALT elevations reflect improvements in liver histology in response to vitamin E therapy. Methods The vitamin E and placebo arms of the Pioglitazone vs. Vitamin E vs. Placebo in Non‐alcoholic Steatohepatitis (PIVENS) trial were reassessed for associations among changes in ALT levels, body weight and liver histology. An ALT response was defined as a decrease to ≤40 U/L and by ≥30% of baseline. Liver biopsies taken before and after treatment were scored for non‐alcoholic fatty liver disease activity (NAS) and fibrosis. Results ALT responses were more frequent among vitamin E (48%) than placebo (16%) recipients (P < 0.001). Among vitamin E recipients, ALT responses were associated with decreases in NAS (P < 0.001), but not fibrosis scores (P = 0.34), whereas among placebo recipients, ALT responses were associated with significant decreases in both (P < 0.05). Weight loss (≥2 kg) was also associated with ALT response (P < 0.001), improvements in NAS (P < 0.001) and fibrosis (P < 0.02), but vitamin E had an added effect both with and without weight loss. Weight gain (≥2 kg) was associated with lack of ALT response and worsening NAS and fibrosis scores in patients not on vitamin E. Conclusions Decrease of ALT levels to normal in patients with NASH is usually associated with improved histological activity. Management should stress the value of weight loss and strongly discourage weight gain. Vitamin E can improve both ALT levels and histology with and without weight loss. Clinical Trial Number: NCT00063622.